Listening from a distance: Experiencing Antarctica in sound art - Carolyn Philpott (2017)
Sounds affect how we feel about places in ways that are immediate and profound. Whether we are outdoors exploring the natural world, or indoors watching a film or television program set in a distant locale, sounds draw our attention to the uniqueness of places and help us to understand the world around us. Although most of us tend to prioritise the visual over the acoustic in our day-to-day lives, music and sound art composed in connection-with places can trigger powerful emotional responses. This, in turn, can make us feel a deeper sense of connection to, and concern for, specific places.